Pengembangan Lembaga Paud Islam Dalam Perspektif Blue Ocean Strategy - Mulyani, Novi; Wiyani, Novan Ardy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to describe and analyze the development of Islamic PAUD institutions carried out by TK ABA Majapahit Kalierang Bumiayu Brebes in the perspective of blue ocean strategy. This research is a naturalist qualitative research. Data were collected using interviews, observation and documentation. Then the data were analyzed using the data analysis technique of the Miles and Huberman model. The results showed that the steps taken in implementing the blue ocean strategy to develop PAUD institutions in TK ABA Majapahit were: (1) Creating a canvas for the development of Islamic PAUD institutions; (2) Create a framework for Islamic PAUD institutions; (3) Create three levels of non-customer Islamic PAUD services; (4) Create a framework for six paths for the development of Islamic PAUD institutions; and (5) Creating the value of innovation in the provision of Islamic PAUD services.